2016
DOI: 10.1590/1807-3107bor-2016.vol30.0036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different fillers on the properties of an experimental vinyl polysiloxane

Abstract: The aim of the study was to evaluate the effect of the incorporation of different fillers on an experimental vinyl polysiloxane (VPS) at two different concentrations, 20% and 40%. Different fillers were added to an experimental VPS. The study was developed in two stages: (i) incorporation of fillers in different concentrations: (a) 20 wt% fillers, and (b) 40 wt%. The fillers were added to experimental VPS and mixed with a speed mixer; (ii) characterization of experimental VPS; after the base paste and catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Many modifications have been proposed in the adhesive resins to contribute to the longevity of the restorative treatments [4][5][6] . A current trend involves the incorporation of inorganic fillers to decrease the relative amount of organic phase, providing a higher hydrolytic stability to resin and a reliable cavity seal [7][8][9][10][11][12] . Besides physical and chemical properties, the addition of inorganic fillers may increase the radiopacity.…”
Section: Introductionmentioning
confidence: 99%
“…Many modifications have been proposed in the adhesive resins to contribute to the longevity of the restorative treatments [4][5][6] . A current trend involves the incorporation of inorganic fillers to decrease the relative amount of organic phase, providing a higher hydrolytic stability to resin and a reliable cavity seal [7][8][9][10][11][12] . Besides physical and chemical properties, the addition of inorganic fillers may increase the radiopacity.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Figure 4 SEM images of Vertex Soft and Dental Gum have smooth fractured surfaces under tension indicating the absence or minimal filler particle content. Meincke et al (2016) reported that polymethyl methacrylate based elastomers have less affinity and less surface activity in comparison with other elastomers with filler contents (Meincke et al, 2016). Dental elastomers tested in the current study which contained fillers showed a higher tensile strength and rougher surface at the fracture interface under tension.…”
Section: Tensilementioning
confidence: 55%
“…and Algin-X Ultra material showed a rough surface SEM with some filler particles being "plucked" from the opposing surface (Figure 4). This may indicate the lack of bonding between filler particles and base elastomer matrix (Klingender, 2008;Meincke et al, 2016). Meincke et al (2016) reported this to be common in silicone materials; fillers must make intimate contact with the elastomer chains if they are going to contribute to reinforcement of the polymer.…”
Section: Tensilementioning
confidence: 99%
“…Figure 5 shows the surface morphology of TPRH and TPS with irregular ( Figure 5 a) and spherical ( Figure 5 b) shape, respectively. The TPS granules with spherical shape caused a reduction in the contact area of the polymer matrix when compared with the irregular shape of TPRH [ 52 ]. For bare polymers of PBS ( Figure 6 a) and PBAT ( Figure 6 b), smooth surface morphology was observed while with filler loading, a rough surface was observed as shown in Figure 6 c–f.…”
Section: Resultsmentioning
confidence: 99%